La Gestion De Calidad Y El Mejoramiento Continuo De Los Procesos Operativos En La Industria De Alimentos Listos Indalist S.A, Del Canton El Carmen Provincia De Manabi Año 2014. - Alcívar Romero, Wilson Lautaro (2014)
Research istheplace in theplantFood IndustryReadyINDALISTSA, which is locatedin theEl Carmen Cantonofthe province of Manabí, which consists of applyingSanitationisdesigned to control, reduce or eliminate pollutionorderto achieve abetter quality of lifefor human beings. One of themeasures usedfor this purposeis based onfood safetythatisjust thecondition of the products,food hasbecome aglobal reference pointfor producersand consumers, becoming a factor,to be competitive inany market. he implementation of Good Manufacturing Practices BPM's serve to get a high quality product, safe for human consumption, using a set of standards designed and used to ensure that the company continue to develop and distribute both nationally and internationally their products, achieving significant improvements in it, helping to lower production costs and selling, maintaining quality in each of the areas is within the requirements of GMP's as seen from the handling, preparation, processing, packaging , storage, transportation and distribution of food for human consumption, ensuring that products manufactured in appropriate sanitary conditions and reducing the risks inherent in the production of products made. This project will comply with a requirement of the Government to continue performing their activities of their products, leaving no doubt that improve internal processes favoring employees and workers, by increasing production because they receive incentives based on it, working beneath quality standards that guarantee them to acquire knowledge and experience in the use of quality tools and our dealers and customers get products that will meet the demands of today's market.